CONSUMER PURCHASE BEHAVIOUR AND BRAND PREFERENCES OF VARIOUS READY TO EAT BREAKFAST CEREALS â€“ A CASE OF HYDERABAD METRO - K. APARNA, G. ALEKYA, SEEMA and (The Journal of Research, PJTSAU, 2019)
Breakfast is regarded by many nutritionists as the most important meal of the day. Breakfast provides a significant proportion of the dayâ€™s total nutrient intake and offers the opportunity to eat food with nutrients, vitamins and fiber. All over the world, cereals are used as staple food and are the cheapest source of energy and protein in human diet. Breakfast cereals are defined as â€œProcessed grain formulations suitable for human consumption without further cookingâ€. In India, majority of food consumption is still at home. Nevertheless, out-of-home food consumption is increasing due to increase in urbanization, breaking up of the traditional joint family system, desire for quality time which translates into an increased need for convenience, increasing number of working women, rise in per capita income, changing lifestyles and increasing level of affluence in the middle income group had brought about changes in food habits (Landstro et.al. 2011)